Designing women's fashion that combines traditional fashion lines in the Kingdom of Saudi Arabia with artistic and contemporary schools - Khomayyis, Arwa Daoud (Journal of Humanities & Social Sciences, 2023)
Arts express culture of nations and their ancient history, and traditional costumes in any nation are a clear and evident reflection of many artistic, social and economic characteristics in any specific historical period, costumes and paintings through ages are artistic practices that affect each other and express the era in which they were found, In general, the twenty-first century and with the transformation of the world into a small village, the knowledge, mixing between the world's cultures and arts from previous historical periods until some new artistic forms appeared and become an expression of the time period that we livin. This study synthesizes and combines the lines of three Saudi Traditional women dresses with three well-known international paintings from different art schools as a feature of the current era expressing synthesis, blending and appreciation arts from all over the world through different historical periods.
Keywords: traditional costumes; fine art schools; culture; synthesis